Comparison of test methods for oxygen permeability: Optical method versus carrier gas method - Müller, Kajetan; Scheuerer, Zuzana; Florian, Veronika; Skutschik, Tina; Sängerlaub, Sven (Polymer testing, 2017)
The oxygen permeability of films is relevant for packaging related and technical applications. An increasingly used test method for the measurement of oxygen permeability is the optical test method, because it allows a simple and cost-efficient measurement setup. This method is based on optical chemical sensors. However, not much is known about its validity. Therefore, method validation is necessary which is subject of this study. The optical method is compared with the carrier gas method for a variety of film samples. In the tested permeability range of 0.5–2500 cm3 (STP)·(m2 d bar)−1 both methods deviated less than 20% for zero and 50% relative humidity. [Display omitted]